Statistics Canada data sources on official-language minorities (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistics Canada, 2009)

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549 -X) - Lafrenière, Sylvie (Statistique Canada, 2013)

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistique Canada, 2009)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

Portrait of Official-Language Minorities in Canada: Francophones in Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistics Canada: Social and Aboriginal Statistics Division, 2010)
This study paints a general statistical portrait of the official-language minority in Ontario based on data from the Census of Population and the Survey on the Vitality of Official-Language Minorities in Canada, conducted in 2006. The purpose of such a portrait is to present a set of characteristics, behaviours and perceptions of the official-language minority population, exploiting the analytical opportunities contained in the data. Section 1 of this demolinguistic portrait concerns the choice of criteria for defining the French-speaking population in Ontario, to be used for the purposes of this study. It also provides a brief description of the data sources used. Section 2 presents varied information on how the French-speaking population has evolved and its geographic distribution and concentration in Ontario. This information is accompanied by a series of maps, appendices and a detailed table on the number, relative weight and distribution of the French-speaking population in Ontario. Section 3 concerns the main factors that affect or are affected by changes over time in this province’s Frenchspeaking population: fertility; the transmission of mother tongue and the effect of exogamy; the age structure; intragenerational linguistic mobility; and interprovincial and international migration. It also provides information on the use of French in the public sphere and on how the ability to conduct a conversation in that language has evolved in groups with a mother tongue other than French or English. Section 4 of this portrait looks at a few sectors essential to the vitality of official-language minority communities, as identified in the Roadmap for Canada's Linguistic Duality 2008-2013: health; justice; education; and the media, the arts and culture. It also provides statistics on community participation, employment and income characteristics, and the use of French at work. The last section of this portrait presents statistics on Francophones’ identity, their perceptions regarding the presence of French in their community, the provision of services in French by the federal government, the respect for linguistic rights, and the perceived importance that people work on developing the Francophone community.
Number of pages: 109

Portrait des minorités de langue officielle au Canada : les francophones de l’Ontario - Corbeil, Jean-Pierre; Lafrenière, Sylvie (Statistique Canada: Division de la statistique sociale et autochtone, 2010)
Cette étude brosse un portrait statistique général de la minorité de langue officielle en Ontario en s’appuyant sur des données du recensement de la population ainsi que sur celles de l’Enquête sur la vitalité des minorités de langue officielle au Canada menée en 2006. Le but d’un tel portrait est de présenter un ensemble de caractéristiques, de comportements et de perceptions de la population de langue officielle minoritaire en mettant en évidence les possibilités d’analyse que recèlent les données. La première section de ce portrait démolinguistique porte sur le choix des critères de définition de la population de langue française en Ontario qui seront utilisés aux fins de ce document ainsi que sur une brève description des sources de données utilisées. La seconde section présente différentes informations qui rendent compte de l’évolution de la population de langue française ainsi que sur la répartition et la concentration de cette population sur le territoire ontarien. Cette information est accompagnée d’une série de cartes géographiques présentée en annexe et d’un tableau détaillé sur l’effectif, le poids relatif et la répartition de la population de langue française en Ontario. La troisième partie porte sur les principaux facteurs qui influent sur l’évolution de la population de langue française dans cette province ou qui en résultent, soit la fécondité, la transmission de la langue maternelle et l’effet de l’exogamie, la structure par âge, la mobilité linguistique intragénérationnelle, la migration interprovinciale et internationale. De plus, on y présente de l’information sur l’usage du français dans la sphère publique et sur l’évolution de la capacité de soutenir une conversation dans cette langue parmi les groupes de langue maternelle autre que française ou anglaise. La quatrième partie de ce portrait porte sur quelques secteurs clés pour la vitalité des communautés de langue officielle en situation minoritaire tels qu’identifiés dans la Feuille de route pour la dualité linguistique canadienne 2008-2013, soit la santé, la justice, l’éducation et les médias, les arts et la culture. Nous y présentons également des statistiques sur la participation communautaire, les caractéristiques de l’emploi et du revenu ainsi que sur l’utilisation du français au travail. Finalement, la dernière partie de ce portrait présente des statistiques sur l’appartenance identitaire des francophones, leurs perceptions à l’égard de la présence du français dans leur communauté, de l’offre de services en français de la part du gouvernement fédéral, du respect des droits ling
Nombre de pages: 114

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)